Development of Square Patch Microstrip Antenna Design by Using Three Dimension Finite Difference Time Domain Methods - Myo Tun, Hla; Pradhan, Devasis; Behera, Manjusha; Su Nwe, Myat; Mon Aye, Su; Than Mon, Aye; Min Naing, Zaw (Journal of Novel Engineering Science and Technology, 2023)
The paper mainly focuses on developing a Square-shaped Microstrip Patch Antenna Design using Three Dimension Finite Difference Time Domain Methods. There have been many time steps for analyzing the electric field in the antenna design. The time step has been started from 0 ps to 1991 ps. The electric field changes from the starting point to the end of the time step prove the analysis of the developed antenna system's input signal and return loss, especially the square-shaped microstrip patch antenna based on the FDTD technique. The simulation results confirm that the fabricated antenna system is a perfect candidate for high-frequency purposes. The analysis has been developed by using MATLAB language.